Death of the iron horse - Goble, Paul. (Bradbury Press, 1987)
In an act of bravery and defiance against the white men encroaching on their territory in 1867, a group of young Cheyenne braves derail and raid a freight train.
In an act of bravery and defiance against the white men encroaching on their territory in 1867, a group of young Cheyenne braves derail and raid a freight train.
SPEC CHIL: In original dust jacket.
Keywords: Cheyenne (North American people) / History / Juvenile fiction. / indig; Railroads / History / Juvenile fiction.; Indians of North America / History / Juvenile fiction.; Cheyenne Indians / History / Juvenile fiction.; Juvenile literature / New York (N.Y.) / 1987 / rbmscv